The investigation of amino acid composition for herbs and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora - T. I. Balanchuk; A. V. Мazulin; Т. V. Оproshanska; G. V. Мazulin (Zaporozhye State Medical University, 2016)
Aim. The investigation of qualitative and quantitative composition of amino acids in flowers and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora during flowering period. Methods and results. HPLC method «ААА 881» (Czech republic) has been used for the analysis of qualitative and quantitative composition. The chromatographic column with cation resin of the brand Ostion LGAN (l=600 mm, d=8,0 mm, column №1) and (l=700 mm, d=7,0 mm, column №2) has been used. Buffered citrate solutions (рН=3,25; 4,25; 5,28) have been used as eluents under working pressure 14-16 kPa/сm2 (column №1) and 4-8 kPa/сm2 (column №2), the amount of the investigated solution - 100 microliters. Results. Presence and accumulation of 15 nonstandard and 15 standard amino acids (up to 11,10+1,22%, 1,47+0,15% in inflorescence; up to 6,72+0,78%; 1,25+0,14% in leaves) has been investigated in herbs and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora. 7 Of them are essential (leucine, isoleucine, methionine, lysine, threonine, phenylalanine, valine). The main identified amino acids in herbs were: cystine (up to 2.01+0.23%), alanine (up to 1.48+0.16%), arginine (up to 1.28+0.11%), lysine (up to 1.14+0.12%). In leaves of Carduus nutans L. and Carduus acanthoides L. the essential amino acid cystine has been revealed in such amount: Carduus nutans L. (up to 1.68+0.15%), Carduus acanthoides L. (up to 1.15+0.13%). Conclusions. The herbs of Carduus nutans L., Carduus acanthoides L. are perspective for obtaining complex phyto-preparations with hepatoprotective and antioxidant activities. Aim. The investigation of qualitative and quantitative composition of amino acids in flowers and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora during flowering period. Methods and results. HPLC method «ААА 881» (Czech republic) has been used for the analysis of qualitative and quantitative composition. The chromatographic column with cation resin of the brand Ostion LGAN (l=600 mm, d=8,0 mm, column №1) and (l=700 mm, d=7,0 mm, column №2) has been used. Buffered citrate solutions (рН=3,25; 4,25; 5,28) have been used as eluents under working pressure 14-16 kPa/сm2 (column №1) and 4-8 kPa/сm2 (column №2), the amount of the investigated solution - 100 microliters. Results. Presence and accumulation of 15 nonstandard and 15 standard amino acids (up to 11,10+1,22%, 1,47+0,15% in inflorescence; up to 6,72+0,78%; 1,25+0,14% in leaves) has been investigated in herbs and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora. 7 Of them are essential (leucine, isoleucine, methionine, lysine, threonine, phenylalanine, valine). The main identified amino acids in herbs were: cystine (up to 2.01+0.23%), alanine (up to 1.48+0.16%), arginine (up to 1.28+0.11%), lysine (up to 1.14+0.12%). In leaves of Carduus nutans L. and Carduus acanthoides L. the essential amino acid cystine has been revealed in such amount: Carduus nutans L. (up to 1.68+0.15%), Carduus acanthoides L. (up to 1.15+0.13%). Conclusions. The herbs of Carduus nutans L., Carduus acanthoides L. are perspective for obtaining complex phyto-preparations with hepatoprotective and antioxidant activities. Aim. The investigation of qualitative and quantitative composition of amino acids in flowers and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora during flowering period. Methods and results. HPLC method «ААА 881» (Czech republic) has been used for the analysis of qualitative and quantitative composition. The chromatographic column with cation resin of the brand Ostion LGAN (l=600 mm, d=8,0 mm, column №1) and (l=700 mm, d=7,0 mm, column №2) has been used. Buffered citrate solutions (рН=3,25; 4,25; 5,28) have been used as eluents under working pressure 14-16 kPa/сm2 (column №1) and 4-8 kPa/сm2 (column №2), the amount of the investigated solution - 100 microliters. Results. Presence and accumulation of 15 nonstandard and 15 standard amino acids (up to 11,10+1,22%, 1,47+0,15% in inflorescence; up to 6,72+0,78%; 1,25+0,14% in leaves) has been investigated in herbs and leaves of Carduus nutans L. and Carduus acanthoides L. of Ukrainian flora. 7 Of them are essential (leucine, isoleucine, methionine, lysine, threonine, phenylalanine, valine). The main identified amino acids in herbs were: cystine (up to 2.01+0.23%), alanine (up to 1.48+0.16%), arginine (up to 1.28+0.11%), lysine (up to 1.14+0.12%). In leaves of Carduus nutans L. and Carduus acanthoides L. the essential amino acid cystine has been revealed in such amount: Carduus nutans L. (up to 1.68+0.15%), Carduus acanthoides L. (up to 1.15+0.13%). Conclusions. The herbs of Carduus nutans L., Carduus acanthoides L. are perspective for obtaining complex phyto-preparations with hepatoprotective and antioxidant activities.